DOMINO GAME APPLICATION DEVELOPMENT - Rijayana, Iwan (CENTRAL ASIA AND THE CAUCASUS, 2022)
Domino is a game that is very well known by the world community. The basic algorithm for creating a domino game application is described in this research. The system will provide a graphical user interface, where the user will perform all the tasks. The result of this research is the creation of an interesting domino game application for users to play.